National occupational safety and health updates 2015 to 2020 towards OSH preventative culture in business organizations in Malaysia - Ab Rahman, Rozanah; Mohd Tamrin, Shamsul Bahri; How, Vivien; Ng, Yee Guan; Zerguine, Haroun (Human Resource Management Academic Research Society, 2019)
Traditionally, neoclassical economics in most of the developing countries are highly dependent on both the private and public sectors for the purposes of policy making. In order to close the gaps that exist in the current OSH policy system, both employers and employees in any business organization are urged to demonstrate full commitment on OSH programs and plans. This paper aimed to summarize the latest OSH policy updates under the government bodies and agencies in Malaysia that affect business activities in all organizations. It is hoped that with these important policies made, the safe and healthy working culture would be positively implemented at the workplaces. To date, the rapid economic transformation in Malaysia requires more proactive insights into the OSH policy and mechanisms, to fulfill the demand of the rapid developmental goals. The summary findings of this OSH report overview could serve as the reference point to understand the development and gaps present from the year 2015 – 2020.